KAJIAN VISUAL PROPERTI SENI PERTUNJUKKAN BUAYA PUTIH - Putra, Yuda Syah (2013)
White Crocodile arts entertainment around the 90's and previously named Crocodile Mangap. Along with the times Crocodile White arts entertainment sustain many changes and developments in function terms and manner of presentation, of course, various of changes that occur from functioning as well as other elements, especially on the material and the visual element at the White Crocodile is very interesting to study . In this research, the authors formulate the problem specifically in the form of a question. First, what a forms, processes and techniques making property of White Crocodile in the Crocodile White art entertainment in Curug Dahu village ? Second, the meaning of what is contained in each element of visual properties of White Crocodile in the White Crocodile art entertaintment in Curug Dahu village ? With the research purpose, to identify and describe forms and processes and techniques are used in the making property White Crocodile in the White Crocodile art in Curug Dahu village. And to know and describe the meaning contained in each visual element on the property White Crocodile in the White Crocodile arts entertaint in Curug Dahu village. The research method used is descriptive method with qualitative approach. Because the data generated in the form of words or verbal from people of associated with the White Crocodile art entertainment . White Crocodile Art is having Islamic traditional arts, as well as cultural heritage that reflects the Curug Dahu village communities. Processes and techniques used in the making property of White Crocodile art entertainment still use the traditional process as well as the materials used was taken from the wild. In each visual element contained in the White Crocodile property has a philosophical meaning functions and adapted to function as a property entertainment in the wedding party. The function of traditional art that has been experiencing a shift should be addressed with wisdom shared by all parties. As a young generation of the nation and we should continue to maintain and preserve the traditional arts as wealth and pride. Besides White Crocodile art can be lifted and published to the wider community. Seni pertunjukkan Buaya Putih ada sekitar tahun 90-an dan sebelumnya bernama Buaya Mangap. Seiring dengan berkembangnya zaman seni pertunjukkan Buaya Putih mengalami banyak perubahan dan perkembangan dari segi fungsi dan tata cara penyajian, tentu saja berbagai perubahan yang terjadi dari fungsi serta unsur-unsur lainnya terutama pada bahan dan unsur visual pada Buaya Putih sangat menarik untuk diteliti. Dalam penelitian ini, penulis merumuskan masalah secara khusus dalam bentuk pertanyaan. Pertama, Bagaimana bentuk, proses dan teknik pembuatan properti Buaya Putih dalam seni pertunjukkan Buaya Putih di kampung Curug Dahu? Kedua, Makna apa yang terkandung dalam setiap unsur visual properti Buaya Putih dalam seni pertunjukkan Buaya Putih di kampung Curug Dahu?. Dengan tujuan penelitian, untuk mengetahui dan mendeskripsikan bentuk serta proses dan teknik yang digunakan dalam pembuatan properti Buaya Putih dalam seni pertunjukkan Buaya Putih di kampung Curug Dahu. Serta untuk mengetahui dan mendeskripsikan makna yang terkandung dalam setiap unsur visual pada properti Buaya Putih dalam seni pertunjukkan Buaya Putih di kampung Curug Dahu. Metode penelitian yang digunakan adalah metode penelitian deskriptif dengan pendekatan kualitatif. Karena data yang dihasilkan berupa kata atau lisan dari orang-orang yang berkaitan dengan seni pertunjukkan Buaya Putih. Kesenian Buaya Putih merupakan kesenian tradisional yang bernafaskan Islam, juga sebagai warisan budaya yang merefleksikan keadaan masyarakat kampung Curug Dahu. Proses dan teknik yang digunakan dalam pembuatan properti seni pertunjukkan Buaya Putih masih menggunakan cara yang tradisional serta bahan-bahan yang digunakkan pun diambil dari alam. Dalam setiap unsur visual yang terdapat dalam properti Buaya Putih memiliki fungsi serta makna filosofis yang disesuaikan dengan fungsinya sebagai properti pertunjukkan dalam pesta pernikahan. Fungsi seni tradisi yang selama ini sudah mengalami pergeseran hendaknya disikapi dengan kearifan bersama oleh seluruh pihak. Sebagai generasi muda dan penerus bangsa kita hendaknya terus menjaga dan melestarikan kesenian tradisional sebagai kekayaan dan kebanggan. Selain itu kesenian Buaya Putih dapat diangkat dan dipublikasikan untuk dikenal masyarakat luas.